Implementation of Srikandi Application: Paperless-Based Digital Transformation of Archives - Rifai, Muchlas; Sugiyanto, Sugiyanto (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
Implementation of the Integrated Archives Information System (Srikandi) Application at the Yogyakarta Harbor Health Office is an important step in supporting digital transformation, especially in the archives sector. With this system, the previously conventional archiving process becomes more efficient and environmentally friendly because it is paperless. Apart from that, the implementation of the Srikandi application is in line with efforts to increase awareness and order in archives which is part of the National Movement for Archives Awareness and Order. The use of the Srikandi application aims to improve effectiveness and efficiency in public services. This research aims to determine the extent of the implementation of the Srikandi Application and the obstacles faced. The theoretical concept used is Charles Edward III's implementation theory, namely communication, resources, disposition, and bureaucratic structure. The research method used is qualitative and is based on interviews, observation, and documentation. The research results show that the implementation of the Srikandi Application at the Yogyakarta Harbor Health Office has been implemented so that the creation of archives is paperless, however, there are still several factors that are obstacles in implementing the Srikandi Application including the quality of human resources, information technology management, and lack of training in the field of archives.